Digital Transformation of Electronic-Based Government System (EBS) in Sukabumi District: Implementation of Central Government Policy to Realise Good Governance - Supriadi, Encep; Ahmad Hunaeni Zulkarnaen; Paminto, Saptaning Ruju; Mulyadi, Dedi (Intellectual Law Review (ILRE), 2024)
The digital transformation of government systems through the Electronic Based Government System (EBS) in Sukabumi District reflects the government's efforts to achieve transparent, accountable, and responsive governance to public needs. This research aims to analyse the implementation of the digitisation policy as well as the challenges faced, including the development of telecommunication infrastructure, human resource skills enhancement, and integration of public service systems. Through qualitative methods and literature study, it was found that the success of SPBE requires not only strong technological infrastructure but also collaboration between central and local governments, as well as training for government employees. The results showed that despite obstacles such as limited infrastructure in remote areas, the strategic measures implemented were able to encourage the creation of a more modern and inclusive government.